O zgodovinskosti in nezgodovinskosti književnih upodobitev mejnih pojavov - Leskovec, Andrea (Primerjalna književnost, 2014)
Borderline experiences can be perceived as an anthropological universal, although their definition and content may differ completely. Literary texts stage borderline experiences as a transgression and transformation of various arrangements in which the author examines the extent to which the staging of borderline phenomena at the level of discourse follows a more or lessuniform structure.
Keywords: literatura; literature; mejna izkušnja; tujost; univerzalnost